Peningkatan Keterampilan Kreatif di Panti Asuhan Omah Katresnan Melalui Program Pelatihan Membatik Tulis dan Ecoprint - Khoiriyah, Alfi; Julianty, Sabrina; Dewi, Anjelika Pingkan Puspita; Jati, Bintang Samudera; Sari, Dwi Anita; Khopsoh, Siti Nur; Saputra, Arya; Sinuraya, Suci Iriani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Omah Katresnan Orphanage faces challenges in creating economic independence due to a lack of human resources to manage businesses and a reliance on donor funds. This community service activity aims to improve the creative skills and independence of foster children through written batik and ecoprint training. The activity involved 25 participants consisting of foster children and orphanage administrators. The implementation method used a community-based training approach consisting of four main stages: observation, socialization, technical training phases 1 and 2, and evaluation. The results showed that participants were able to understand and apply basic batik techniques (using canting, coloring) and ecoprint techniques (selecting natural motifs, hammering). In addition to producing economically valuable products such as tote bags and decorative fabrics, the program succeeded in increasing participants' self-confidence, creativity, and cultural awareness. This program recommends sustainable independent practice by the orphanage to strengthen entrepreneurial potential in the future.